DEVELOPMENT OF VIDEO TUTORIAL MEDIA ON HALF CIRCLE SKIRT MODEL - Halida Hanim,; Hotmaria Tampubolon,; Eka Rahma Dewi,; Yudhistira Anggraini, (International Journal of Innovative Technologies in Social Science, 2023)
The aim of this research is: (1) Develop a video media tutorial for a semi-circle skirt model in women's basic fashion courses in the fashion study program (2) Knowing the feasibility and effectiveness of the semi-circle skirt model video tutorial learning media in the women's basic fashion course in the fashion study program.This study uses the ADDIE development model. The results of this development research are in the form of a learning video product to make a semi-circle skirt. In this study, the feasibility test was carried out by 2 media experts and 2 material experts. The media effectiveness test was carried out in three stages, namely, a small-scale group test conducted by 8 students, a medium-scale group test conducted by 16 students and a large-scale group test conducted by 33 students. The results of the validity of the material experts obtained an average rating of 90.6% in the "very good" category. the results of the validity of media experts obtained an average rating of 94.2% in the "very good" category. small group trials by students got the "Good" category with an average of 80.7%. Medium group trials by students got the "Good" category with an average of 85%. large group trials by students got the "Good" category with an average of 87.4%.The results of the research on the development of learning media based on video tutorials on semi-circular skirts were declared feasible and effective to be used as learning media in women's basic clothing courses in the material of making semi-circular skirts